1992
DOI: 10.1136/gut.33.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Aminopyrine breath test in the prognostic evaluation of patients with cirrhosis.

Abstract: analysis, a prognostic index cut off value of 2-6 had a 94% sensitivity and a 88% specificity. The prognostic index significantly improved prognostic accuracy when compared with a prognostic index calculated from Pugh score and aetiology, but excluding aminopyrine breath test (p=0.05). These data disclose that the aminopyrine breath test offers additional prognostic information to the Pugh score, and it may become a useful tool to better assess the prognosis of patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…In terms of prognostication, studies have shown that these tests offer little, if any, additional predictive information when compared with more traditional assessment such as the Child-Pugh score. [23][24][25][26][27] The results from the present study support the application of the CBT as a test of quantitative liver assessment. Our data indicate that: (1) the elimination of caffeine is impaired in cirrhosis, characterized by a reduction in plasma clearance and a prolongation in caffeine half-life; (2) the oral 13 C-CBT using a single 1-hour measure correlates very closely with plasma caffeine clearance; (3) cirrhotic subjects show significantly reduced CBT results compared with control and hepatitic subjects; (4) CBT values are increased in smokers but still distinguish smokers of varying hepatic functional impairment; (5) the CBT appears to be a reproducible assay; and, (6) the CBT is administered easily and safely in subjects with liver disease.…”
Section: Discussionsupporting
confidence: 55%
“…In terms of prognostication, studies have shown that these tests offer little, if any, additional predictive information when compared with more traditional assessment such as the Child-Pugh score. [23][24][25][26][27] The results from the present study support the application of the CBT as a test of quantitative liver assessment. Our data indicate that: (1) the elimination of caffeine is impaired in cirrhosis, characterized by a reduction in plasma clearance and a prolongation in caffeine half-life; (2) the oral 13 C-CBT using a single 1-hour measure correlates very closely with plasma caffeine clearance; (3) cirrhotic subjects show significantly reduced CBT results compared with control and hepatitic subjects; (4) CBT values are increased in smokers but still distinguish smokers of varying hepatic functional impairment; (5) the CBT appears to be a reproducible assay; and, (6) the CBT is administered easily and safely in subjects with liver disease.…”
Section: Discussionsupporting
confidence: 55%
“…16 The cut-off levels for the most important parameters are listed in Table 1. For ALT, three different cut-off levels were used: the upper limit of normal set by the biochemistry laboratory (56 IU l À1 ), the classical cut-off of 40 IU l À124 and the limits proposed by Prati et al 25 (30 IU l À1 in men, 19 IU l À1 in women).…”
Section: Methodsmentioning
confidence: 99%
“…14 The liver specific program, approved by the Ethics Committee of the University Hospital Antwerp, includes additional blood analysis to exclude the classical etiologies of liver disease (for example, viral hepatitis and autoimmune disease); a Doppler ultrasound of the abdomen; a liver-spleen scintigraphy 15 and an aminopyrine breath test as a measure for liver metabolic reserve. 16 As liver steatosis seems to be closely related to the metabolic syndrome (MS), 17 features of the MS were specifically recorded. According to the US Third Adult Treatment Panel of the National Cholesterol Education Program, 18 the MS is defined as the presence of three or more out of the five known criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The first risk of death, but, when a time-dependent model was Prentice's criterion is proven by the strict association of defitted containing galactose elimination capacity and per-crease in quantitative liver function tests and survival shown sistent alcohol abuse, only the former remained signifi-in many series. [6][7][8] The adherence to the second criterion is cant. This implies that variations in the risk of death more difficult to prove, and should be assessed for any single occurring as a consequence of abstinence from alcohol treatment.…”
mentioning
confidence: 99%